Isolation and Characterization of Polyprenols from Litsea monopetala (Roxb.) Pers. - Kamal, Mir Shahriar; Ashrafi, Sania; Sultana, Sara; A Rashid, Mohammad; Ahsan, Monira; Masud, Mohammad Mehedi; Haque, Mohammad Rashedul (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Litsea monopetala (Roxb.) Pers. (Family: Lauraceae) is a plant that holds substantial ethnobotanical significance due to its traditional and cultural importance. In this study, we conducted an extensive chemical investigation on L. monopetala, a plant native to the regions including Nepal, India, and Bangladesh. Two unique secondary metabolites were isolated and characterized from ethyl acetate (EtOAc) extract of the leaves of L. monopetala which were identified as tri-trans poly-cis prenol-15 (1), and its acetylated derivative tri-trans poly-cis prenol-15 (2). The structures of the isolated compounds were determined through in-depth analysis of their highresolution 1H NMR, 13C NMR, COSY, HSQC, and HMBC spectroscopic data, along with comparison to existing published data. Both the compounds are isolated from the plant for the first time. Further studies are recommended to analyze the potential bioactivity associated with the molecules. Dhaka Univ. J. Pharm. Sci. 23(1): 63-68, 2024 (June)